2021
DOI: 10.1002/ece3.8226
|View full text |Cite
|
Sign up to set email alerts
|

(Non)Parallel developmental mechanisms in vertebrate appendage reduction and loss

Abstract: Appendages have been reduced or lost hundreds of times during vertebrate evolution. This phenotypic convergence may be underlain by shared or different molecular mechanisms in distantly related vertebrate clades. To investigate, we reviewed the developmental and evolutionary literature of appendage reduction and loss in more than a dozen vertebrate genera from fish to mammals. We found that appendage reduction and loss was nearly always driven by modified gene expression as opposed to changes in coding sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 161 publications
(428 reference statements)
2
6
0
Order By: Relevance
“…In conclusion, the limited evidence for use of altered Pitx1 expression in hindlimb reduced squamates may result from the absence of the hindlimb‐specific enhancer, PelA , small effects of PelB , or the adverse pleiotropic effects of a disrupted Pen enhancer. Our findings are consistent with available evidence from non‐model organisms that there are multiple developmental and molecular routes to hindlimb reduction (Roscito et al, 2022; Swank et al, 2021). Consequently, hindlimb loss is likely non‐parallel in squamates and Pitx1 is only one of the several genetic pathways that could be used to respond to similar selection pressures.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In conclusion, the limited evidence for use of altered Pitx1 expression in hindlimb reduced squamates may result from the absence of the hindlimb‐specific enhancer, PelA , small effects of PelB , or the adverse pleiotropic effects of a disrupted Pen enhancer. Our findings are consistent with available evidence from non‐model organisms that there are multiple developmental and molecular routes to hindlimb reduction (Roscito et al, 2022; Swank et al, 2021). Consequently, hindlimb loss is likely non‐parallel in squamates and Pitx1 is only one of the several genetic pathways that could be used to respond to similar selection pressures.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a recent comparative genomics study of three limb‐reduced reptile lineages found that the molecular basis of limb loss was not convergent and in no lineage was Pitx1 a major driver (Roscito et al, 2022). In this study, we corroborate the findings of Swank et al (2021) and Roscito et al (2022) with new data collected from six lizard clades that independently evolved hindlimb reduction. We tested for Pitx1 ’s signature of left‐larger asymmetry in vestigial hindlimbs and found left‐larger asymmetry in only one species.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations